Peggy Glanville-Hicks : Composer and Critic - Robinson, Suzanne, 1963- (Book collections on Project MUSE., 2019)
"As both composer and critic, Peggy Glanville-Hicks contributed to the astonishing cultural ferment of the mid-twentieth century. Her forceful voice as a writer and commentator helped shape professional and public opinion on the state of American composing. The seventy musical works she composed ranged from celebrated operas like Nausicaa to intimate, jewel-like compositions created for friends. Her circle included figures like Virgil Thomson, Paul Bowles, John Cage, and Yehudi Menuhin. Drawing on interviews, archival research, and fifty-four years of extraordinary pocket diaries, Suzanne Robinson places Glanville-Hicks within the history of American music and composers. "P.G.H."--affectionately described as "Australian and pushy"--forged alliances with power brokers and artists that gained her entrance to core American cultural entities such as the League of Composers, New York Herald Tribune, and the Harkness Ballet. Yet her impeccably cultivated public image concealed a private life marked by unhappy love affairs, stubborn poverty, and the painstaking creation of her artistic works. Evocative and intricate, Peggy Glanville-Hicks clears away decades of myth and storytelling to provide a portrait of a remarkable figure and her times."--ProQuest.